Long-term impacts of environmental policy and eco-innovative activities of firms - Rennings, Klaus; Rexhäuser, Sascha (Mannheim, 2010)
"This paper investigates two central questions. Are there long-term effects of regulation on innovation? Does the impact of different types of regulation differ by type of the environmental benefit of the innovations? The overwhelming majority of regulations considered in this paper are of the command-and-control type, and thus, non-market based. The theoretical literature offers clear arguments, why command-and-control regulations are not dynamically efficient, which means that they do not provide a sufficient amount of long-term innovative incentives compared to market based instruments. One possible explanation might be that there is no further need to adapt after a given performance standard is achieved. Nevertheless, a notable amount of firms stated in the European Community Innovation Survey (CIS) that environmentally related innovations have been introduced in response to regulations from the 1950s and 1970s. Therefore, contrary to conventional wisdom, non-market based regulation might also provide a certain amount of long-term innovative incentives. The present study uses data from the German part of the CIS in 2009, the Mannheim Innovation Panel (MIP). Evidence for nine different classes of environmental benefits of introduced innovations is provided by a question where firms were asked to state the amount of environmental benefits (ranging between no, low, medium, and high benefits). Furthermore, firms were asked about the determinants of these innovations. The focus in this paper is only on governmental regulation. In cases where innovations are introduced due to regulatory constraints, firms were asked to cite the respective laws to be responsible for these innovations. These laws were classified into three major fields of environmental policy and furthermore, the effective dates of these laws were identified. Almost all of the cited regulations are nonmarket based. The ordered probit estimation approach used in this paper provides only limited support for innovative effects of these three policy types in general. They only trigger environmentally related innovations for strongly related environmental aspects. In addition to this finding, the results provide evidence for long-term innovative effects of command-and-control regulation. However, such long-term effects of regulation on environmentally related innovation do not exist for all of the examined environmental benefits of innovations."